Increased anxiety in children and adolescents who witnessed military conflict: comparative analysis, prognosis - Tokarchuk Анастасія; Koval Ірина (Psychosomatic Medicine and General Practice, 2024)
The aim of study. The study of the state of mind of Ukrainian children and adolescents for the period 2014-2024, since it is children who are still undergoing physiological development and, especially, the formation of the nervous system, who are the most vulnerable category of the population under the influence of stressors, especially in war conditions, and comparison of the results with data on mental changes in children from equal countries of the world where there were hostilities. Methods. We analyzed the literature on the topic published over the past 5 years. To search for literature, we used such databases as PubMed, APA PsychNet, Google Scholar, Scopus, and Web Of Science. The study was conducted at the National Children’s Specialized Hospital “OHMATDYT” of the Ministry of Health of Ukraine in compliance with all ethical standards and requirements, as well as with the consent of parents or guardians to collect information. The study involved children who were exposed to psychotraumatic events during the Russian-Ukrainian military conflict from 2013 to 2022 after the full-scale invasion from 2022 to 2024. Average age of patients: 10.8 years old - children who witnessed the military conflict of 2014-2023 and 13.5 years old - children who witnessed or participated in the full-scale invasion of 2022-2024. 55.3% of them were girls and 44.7% of boys (2013-2014); 59.2% of girls and 40.7% of boys (2022-2024), respectively. The Hospital Anxiety and Depression Scale (HADS) and the Spielberger-Hanin Anxiety Rating Scale (STAI) were used for the main stage of the study. The results. According to the results of the Hospital Anxiety and Depression Scale (HADS) study, anxiety scores increased by 51.55% and depression scores by 33.83% between 2014 and 2024. As of today, the level of anxiety and depression meets the criteria for subclinical and clinical manifestations. The results of the study for the period 2014-2024 using the Spielberger-Hanin Anxiety Rating Scale show an increase in situational anxiety by 26.7%, and personal anxiety, respectively, by 22.6%. According to statistical data for the period 2023-2024, 18.5% of children have officially diagnosed and confirmed by a psychiatrist anxiety-phobic or anxiety-depressive disorder, and 7.5% had other mental disorders (schizoaffective disorders, psychopathy, bipolar personality disorder). Thus, at least a quarter of children (18.5+7.5=26%) have significant mental disorders, most of which were detected in early puberty, without a burdensome family history. Conclusions. Summarizing the findings of the study, we can state that the level of anxiety and depression in children due to the Russian-Ukrainian military conflict has increased significantly in 2014-2024. Also, during the period of the full-scale invasion, children’s levels of situational (+26.7%) and personal (22.6%) anxiety increased significantly. That is, today, depression rates reach subclinical levels, and anxiety reaches clinical, diagnostic manifestations, which gives us reason to study the problem further in order to develop an adequate algorithm for providing medical, psychological and social rehabilitation assistance.